High-performance absorber with substitutable materials for short-wave infrared sensing - Li, Fengjie; Wang, Shang; Chi, Zongtao; Zhang, Tiqiang; Yu, Ruitao; Wang, Bin; Li, Ning (Frontiers in Astronomy and Space Sciences, 2024)
The optical absorption device plays a crucial role as a component of the infrared astronomical telescope and possesses a significant impact on astronomical observations. A simple metamaterial absorber with substitutable middle materials is made for short-wave infrared sensing. The absorber is designed as a hollow square column, using a patterning approach for the top-layer structure of metamaterials. The absorption characteristics are verified using the impedance matching method, which involves extracting S-parameters and then performing inverse calculations to determine the absorber’s equivalent impedance. The result shows the highest absorption peak is at 3.25 μm, reaching 99.71%, with an impressive average absorption rate of 99.01% between 1.52 and 3.66 μm. The results demonstrate that this absorber shows polarization insensitivity while maintaining high absorption even at large angles of incidence. The distribution of the electromagnetic field within the absorber, the electromagnetic losses within individual layers, and their impact on the absorptive performance are analyzed in detail. Polarization angles, transverse magnetic polarization, and transverse electric polarization are further explored. The parameters of each layer have been discussed. An investigation of the intermediate dielectric layer has been conducted. The proposed absorber shows the potential to achieve exceptional absorption performance under various dielectric conditions, rendering it a promising candidate for use in astronomical observation, medical tests, infrared detection, invisible short-wave infrared systems, radar and various optical devices.